Ilmu Komunikasi PERSEPSI REMAJA DESA BARU LADANG BAMBU TERHADAP TAYANGAN FILM DUA GARIS BIRU - Arya Dwi Putra (UNIVERSITAS STEKOM, 2023)
Cinema is one form of entertainment that is increasingly popular and in great demand. More than that, film is a social text that simultaneously captures and talks about the dynamics of people's lives at the time the film was produced. Film descriptions and narratives can be said to be windows that are quite meaningful to see and understand social reality that occurs in a certain time and space. The film Two Blue Stripes is a film about teenage sisters. This film is interesting to study because it describes the reality of the problems of Indonesian youth. Teen associations have many positive and negative impacts depending on how a teenager chooses friends based on each individual. This study employed qualitative methods using data collection techniques including observation. In this study the observation method was carried out by collecting and sending to the research site. It can be concluded that the film Dua Garis Biru, which was shown in cinemas, had a great influence on the perceptions of adolescents in the area, such as negative perceptions. the impact of teenage association, especially sex outside of marriage, adolescence is a period of transition from childhood to adulthood and requires guidance from teachers and parents so that their sons and daughters do not fall into bad associations. Keywords: Youth, Cinema Film, Two Blue Lines